Integration of the ubiquitin-proteasome pathway with a cytosolic oligopeptidase activity. - Wang, E; Kessler, B; Borodovsky, A; Cravatt, B; Bogyo, M; Ploegh, H; Glas, R (2000)
Cytosolic proteolysis is carried out predominantly by the proteasome. We show that a large oligopeptidase, tripeptidylpeptidase II (TPPII), can compensate for compromised proteasome activity. Overexpression of TPPII is sufficient to prevent accumulation of polyubiquitinated proteins and allows survival of EL-4 cells at otherwise lethal concentrations of the covalent proteasome inhibitor NLVS (NIP-leu-leu-leu-vinylsulfone). Elevated TPPII activity also partially restores peptide loading of MHC molecules. Purified proteasomes from adapted cells lack the chymotryptic-like activity, but still degrade longer peptide substrates via residual activity of their Z subunits. However, growth of adapted cells depends on induction of other proteolytic activities. Therefore, cytosolic oligopeptidases such as TPPII normalize rates of intracellular protein breakdown required for normal cellular function and viability.